1990
DOI: 10.1093/carcin/11.9.1663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotine and tobacco-specific nitrosamines on the metabolism of N'-nitrosonornicotine and 4-(methylnitrosamino)-1-(3pyridyl)-1-butanone by rat oral tissue

Abstract: The effect of N'-nitrosoanatabine (NAT) and nicotine on the metabolism of N'-nitrosonornicotine (NNN) and 4-(methyl-nitrosamino)-1-(3- pyridyl)-1-butanone (NNK) by cultured rat oral tissue was investigated. The effect of NNN on NNK metabolism and the effect of NNK on NNN metabolism was also determined. NNK inhibited NNN metabolism more than NNN inhibited NNK metabolism. NAT inhibited the metabolism of NNK but not of NNN. Nicotine, which is present at greater than 500 times the levels of NNN and NNK in smokeles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 0 publications
7
44
0
Order By: Relevance
“…Exposure to nicotine caused a statistically significant increase in micronucleus frequency in human gingival fibroblasts in vitro [25]. However, it has been demonstrated that nicotine inhibits the action of nitrosamines which is catalyzed by P450 2E1 [26,27], and also it participates in the conversion of benzo[a]pyrene to DNA-reactive metabolites [28]. Nitrosamines and polycyclic aromatic amines are considered important chemical agents able to promote genetic insult as far as carcinogenesis [15].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to nicotine caused a statistically significant increase in micronucleus frequency in human gingival fibroblasts in vitro [25]. However, it has been demonstrated that nicotine inhibits the action of nitrosamines which is catalyzed by P450 2E1 [26,27], and also it participates in the conversion of benzo[a]pyrene to DNA-reactive metabolites [28]. Nitrosamines and polycyclic aromatic amines are considered important chemical agents able to promote genetic insult as far as carcinogenesis [15].…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro studies have shown that 2′-hydroxylation of NNN is favored in rat esophagus compared to 5′-hydroxylation (13)(14)(16)(17), and POB-DNA adducts derived from NNN 2′-hydroxylation have been detected in rat esophagus cultured with [5-3 H]NNN, as measured by HPB released by acid hydrolysis (10). The results of the current study are consistent with these findings and demonstrate for the first time the in vivo formation of POB-DNA adducts in the esophagus of NNN-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Structures of POB-DNA adducts (10)(11)(12)(13)(14)(15) and DNA adducts derived from 5′-hydroxylation of NNN (16 and 17). dR: 2′-deoxyribosyl.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, experiments were performed to investigate wether nicotine and its main metabolite cotinine affect NNK metabolism in intact organs. In several studies nicotine has been shown to inhibit the metabolic activation of NNK in vivo (Richter and Tricker 1994;Kutzer et al 1995) and in vitro (Murphy and Heiblum 1990;Hong et al 1992).…”
Section: Discussionmentioning
confidence: 99%